Locked up - Watson, Cristy, 1964- (SideStreets., 2019)
"When he was fifteen, Kevin took a car for a joyride and got in an accident that seriously injured a pedestrian. Known inside juvenile detention as Strider, he has spent more than two years incarcerated, and has learned the hard way how to survive inside. Strider keeps his head down and continues his schoolwork, and another inmate called Wired gives Strider protection from the gangs in exchange for loans of money and helping Wired cheat on tests. When his parole officer suggests that he apply for early parole, Strider realizes that it would be hard for him to survive on the outside. All the kids he knew have moved on without him, and he has nothing to return to but life with his father since his mother left them. When Strider sees Wired's sister Larkyn come to visit her brother, he is very attracted to her. Maybe with someone like her, Strider can learn how to get by when he gets out. But his hopes that there might be a life for him after juvie are dashed when it becomes clear that Larkyn is just bait to get Strider to bring in contraband for Wired to distribute. Riddled with guilt, Strider feels he doesn't deserve to ever be let out, because he ruined his own life and the life of the victim of the car accident. But then he gets a visit from Aisha, the daughter of the man who was injured in the accident. With Aisha's help, can Strider forgive himself and try to make a life on the outside?"--